Effect of a participatory multisectoral maternal and newborn intervention on birth preparedness and knowledge of maternal and newborn danger signs among women in Eastern Uganda: a quasi-experiment study. (1st August 2017) - Muhumuza Kananura, Rornald; Tetui, Moses; Bua, John; Ekirapa-Kiracho, Elizabeth; Mutebi, Aloysius; Namazzi, Gertrude; Namusoke Kiwanuka, Suzanne; Waiswa, Peter
ABSTRACT: Background: Knowledge of obstetric danger signs and adequate birth preparedness (BP) are critical for improving maternal services utilization. Objectives: This study assessed the effect of a participatory multi-sectoral maternal and newborn intervention on BP and knowledge of obstetric danger signs among women in Eastern Uganda. Methods: The Maternal and Neonatal Implementation for Equitable Systems (MANIFEST) study was implemented in three districts from 2013 to 2015 using a quasi-experimental pre–post comparison design. Data were collected from women who delivered in the last 12 months. Difference-in-differences (DiD) and generalized linear modelling analysis were used to assess the effect of the intervention on BP practices and knowledge of obstetric danger signs. Results: The overall BP practices increased after the intervention (DiD = 5, p < 0.05). The increase was significant in both intervention and comparison areas (7–39% vs. 7–36%, respectively), with a slightly higher increase in the intervention area. Individual savings, group savings, and identification of a transporter increased in both intervention and comparison area (7–69% vs. 10–64%, 0–11% vs. 0–5%, and 9–14% vs. 9–13%, respectively). The intervention significantly increased the knowledge of at least three obstetric danger signs (DiD = 31%) and knowledge of at least two newborn danger signs (DiD = 21%). Having knowledge of at least three BP components and attending community dialogue meetings increased the odds of BP practices and obstetric danger signs' knowledge, respectively. Village health teams' home visits, intervention area residence, and being in the 25+ age group increased the odds of both BP practices and obstetric danger signs' knowledge. Conclusions: The intervention resulted in a modest increase in BP practices and knowledge of obstetric danger signs. Multiple strategies targeting women, in particular the adolescent group, are needed to promote behavior change for improved BP and knowledge of obstetric danger signs.